Characterization of Anthocyanins From Intraspecific Crosses of Monastrell With Other Premium Varieties - Gil-Muñoz, R.; Moreno-Olivares, J. D.; Paladines-Quezada, D. F.; Bleda-Sánchez, J. A.; Cebrían-Pérez, A.; Giménez-Bañón, M. J.; Fernández-Fernández, J. I. (Frontiers in Nutrition, 2021)
One way in which the wine sector is reacting to the challenge of climate change is to develop plant material that is adapted to the new conditions. Such a strategy will allow the continuation of quality viticulture in traditional winemaking areas that will otherwise be abandoned. The objective of this study was to characterise the anthocyanin composition and content of selected intraspecific hybrids of Monastrell with two other varieties (Syrah and Cabernet Sauvignon). The experiment was carried out over three successive seasons, and the polyphenolic quality of the grapes and wines was assessed along with the adaptation of the hybrids to the high temperatures which will inevitably affect our area (south-eastern Spain). The results showed that, compared with grapes of the Monastrell variety and the wines made from them, most of the hybrids (MS10, MS34 and MC111) had a higher total anthocyanin concentration and overall content of acylated anthocyanins, depending on the year studied. KEYWORDS: Intraspecific hybrids, Monastrell, grapes, wine, anthocyanins